Informal ready-to-eat food vending: A social practice perspective on urban food provisioning in Nigeria - Adeosun, Kehinde Paul; Greene, Mary; Oosterveer, Peter (Springer, 2022)
The way people access food in Nigeria is of central relevance for food security, health and sustainability. One key trend is the shift from household-based to primarily out-of-home food consumption as an increasing majority of the urban poor derive their daily nutrient intake from street foods. However, few studies have yet explored the role of the ready-to-eat food vending sector in urban food systems and the diets of the urban poor. This paper investigates the interrelations between these practices and the diversity of food groups provisioned among the urban poor in developing city contexts. A social practice approach is employed to explore differentiation among informal-ready-to-eat food vending practices in the city of Ibadan, Nigeria, in terms of their daily activities, competences and resources. Applied methods include GIS mapping, food log diaries, in-depth interviews and participant observation to map and classify informal-ready-to-eat food vending practices according to the nature of food provisioned and explore the everyday performances of different informal-ready-to-eat food vending practice initiatives and their relation to dietary diversity. The results reveal three key categories among these practices: traditional, processed and unprocessed—with varying levels of diversity in the food groups on offer. Traditional food vendors offer more diversified food compared to processed food vendors and unprocessed food vendors. The results reveal that material infrastructure, cooking bargaining and purchasing skills and nutritional knowledge are key to the diversity of food groups provisioned. The paper concludes by considering the wider relevance of these findings for urban food science and policy.